Tibial lengthening using a retrograde magnetically driven intramedullary lengthening device in 10 patients with preexisting ankle and hindfoot fusion - Vogt, Bjoern (Acta Orthop, 2020)
Background and purpose — Motorized intramedullary lengthening nails (ILNs) have been developed as an alternative to external fixators for long bone lengthening. The antegrade approach represents the standard method for tibial ILN insertion. In patients with preexisting ankle and hindfoot fusion a retrograde approach provides an alternative technique that has not been evaluated so far. We report the outcome of this method in 10 patients. Patients and methods — This retrospective study included 10 patients (mean age 18 years [13–25]) with preexisting ankle and hindfoot fusion who underwent tibial lengthening with a retrograde ILN (PRECICE). The mean leg length discrepancy (LLD) was 58 mm (36–80). The underlying conditions were congenital (n = 9) and post tumor resection (n = 1). The main outcome measures were: ILN reliability, distraction achieved, distraction index (DIX), time to bone healing, consolidation index (CIX), complications, and functional results. Results — All patients achieved the goal of lengthening (mean 48 mm [26–80]). Average DIX was 0.6 mm/day (0.5–0.7) and mean CIX was 44 days/cm (26–60). Delayed consolidation occurred in 2 patients and healed after ILN dynamization or nail exchange with grafting. Toe contractures in 2 other patients were resolved with physiotherapy or tenotomy. Until last follow-up (mean 18 months [12–30]) no true complications were encountered, knee motion remained unaffected, and full osseous consolidation occurred in all patients. Interpretation — In patients with LLD and preexisting ankle and hindfoot fusion distal tibial lengthening using a retrograde ILN is a reliable alternative to the standard approach with equivalent bone healing potential and low complication rates leaving the knee unaffected.